Social reading platforms, applications, clouds and tags - Cordón García, José Antonio; Alonso Arévalo, Julio; Gómez Díaz, Raquel; Linder, Daniel (Information professional series, 2013)
"Contemporary developments in the book publishing industry are changing the system as we know it. Changes in established understandings of authorship and readership are leading to new business models in line with the postulates of Web 2.0. Socially networked authorship, book production and reading are among the social and discursive practices starting to define this emerging system. Websites offering socially networked, collaborative and shared reading are increasingly important. Social Reading maps socially networked reading within the larger framework of a changing conception of books and reading. This book is structured into chapters covering topics in: social reading and a new conception of the book; an evaluation of social reading platforms; an analysis of social reading applications; the personalization of system contents; reading in the Cloud and the development of new business models; and Open Access e-books. Discusses social reading as an emerging tendency involving authors, readers, librarians, publishers, and other industry professionals -- Describes how the way we read is changing -- Presents ways in which the major players in the digital content industry are developing specific applications to foster socially networked reading."--Provided by publisher